2021
DOI: 10.1080/10942912.2021.1879133
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Selection Attributes Affecting Pet Food Purchase: After COVID-19 Pandemic

Abstract: This study aimed to test empirically a theoretical model defining the selection attributes of pet food, which are increasing notably in Korea. The proposed model incorporates three phases: Selection attributes, recommendation and attitude, and purchase intention. A total of 450 questionnaires were issued, and the survey results were analyzed to verify the reliability and validity of the measured variables. A Structural Equation Model (SEM) was used to test the hypotheses of the study. The results showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(76 reference statements)
2
1
0
Order By: Relevance
“…Veterinarian studies have found that pet owners actively seek specific product attributes when purchasing pet food and consider their vet and the Internet as essential information sources when it comes to pet food purchases [ 19 , 41 ]. These findings have been confirmed by Park and Um (2021) and Kwak and Cha (2021) in their research on pet food purchases and consumer behaviour in times of COVID-19 [ 25 , 42 ]. Park and Um’s research (2021) adds value to the body of literature on pet food [ 25 ], as the study presents consumer clusters based on varying degrees of interest and involvement in pet food purchasing.…”
Section: Introductionsupporting
confidence: 59%
“…Veterinarian studies have found that pet owners actively seek specific product attributes when purchasing pet food and consider their vet and the Internet as essential information sources when it comes to pet food purchases [ 19 , 41 ]. These findings have been confirmed by Park and Um (2021) and Kwak and Cha (2021) in their research on pet food purchases and consumer behaviour in times of COVID-19 [ 25 , 42 ]. Park and Um’s research (2021) adds value to the body of literature on pet food [ 25 ], as the study presents consumer clusters based on varying degrees of interest and involvement in pet food purchasing.…”
Section: Introductionsupporting
confidence: 59%
“…Furthermore, product characteristics: brand reputation, nutrition, packaging and quantity are more considerable than price and marketing on consumer's decision. This show the similarity to the study in Korea from Kwak and Cha (2021), the author finds that brand reputation, perception of product healthiness as well as price fairness have a positive effect on consumers' attitude toward pet food purchasing. Packaging, price and product healthiness influence the purchasing behavior for offline customers while only price influences online customers.…”
Section: Pet Food Consumptionsupporting
confidence: 79%
“…Beyond direct comparative presentation of food, dog preference is often assessed through owner reports. These studies often relate how the owner sees their dog holistically “enjoying” a food product to their preference for obtaining that product [ 8 , 9 , 10 ]. Several factors have been shown to influence owner motivation to feed a product.…”
Section: Introductionmentioning
confidence: 99%